Transarterial Chemoembolization Combined With Radiofrequency Ablation Versus Repeat Hepatectomy for Recurrent Hepatocellular Carcinoma After Curative Resection: A 10-Year Single-Center Comparative Study - Zheng, Xin; Ren, Yanqiao; Hu, Hanqing; Qian, Kun (Frontiers in Oncology, 2021)
Background: The purpose of this study was to compare the efficacy and safety of transarterial chemoembolization (TACE) in combination with radiofrequency ablation (RFA) (TACE-RFA) and repeat hepatectomy in the treatment of recurrent hepatocellular carcinoma (HCC) after curative resection. Methods: This retrospective study evaluated consecutive medical records of patients who received either TACE-RFA or repeat hepatectomy between January 2010 and May 2021. Overall survival (OS), progression-free survival (PFS), and complications were compared. Meanwhile, subgroup analysis was conducted according to the tumor diameter to explore the efficacy of the two groups of patients with tumor diameter > 5cm. Results: Of the 2672 patients who received either TACE-RFA or repeat hepatectomy, 111 eligible patients were included in our study, 63 in the TACE-RFA group and 48 in the repeat hepatectomy group. The median OS was 38 months in the TACE-RFA group and 42 months in the repeat hepatectomy group, with no statistically significant difference between the two groups (P=0.45). Meanwhile, there was also no statistically significant difference in PFS between the two groups (P=0.634). Subgroup analysis showed comparable outcomes in patients with recurrent HCC with tumors > 5cm in diameter. Although both groups achieved similar outcomes, the rate of major complications was significantly higher in the repeat hepatectomy group than in the TACE-RFA group (P=0.003). Conclusions: Patients with recurrent HCC in the TACE-RFA group and the repeat hepatectomy group had similar OS and PFS regardless of the patient's tumor diameter, but the TACE-RFA group was safer and more minimally invasive.